A discourse analysis of the macro-structure, metadiscoursal and microdiscoursal features in the abstracts of research articles across multiple science disciplines. - Sing Bik Cindy Ngai; Rita Gill Singh; Alex Chun Koon (PLoS ONE, 2018)
The abstract of a scientific research article convinces readers that the article deserves to be read. Abstracts can also determine the success of publications and grant applications. In recent years, there has been a trend of cross-disciplinary collaborations in the science community. Scientists have been increasingly expected to engage not only experts of their own disciplines, but also other disciplines with the scope of interest extending to non-experts, such as policy-makers and the general public. Thus, the macro-structure, metadiscoursal and microdiscoursal features exhibited in scientific article abstracts merit attention. In our study, we examined 500 abstracts of scientific research articles published in 50 high-impact journals across five science disciplines (Earth, Formal, Life, Physical and Social Sciences), and performed quantitative analysis of the move structure as well as use of boosters and linguistic features. We found significant interdisciplinary variations in the move structure, boosters and linguistic features employed by these science disciplines. We confirmed that each science discipline possesses a distinct set of macro-structural, metadiscoursal and formalization features, which contribute to its own unique discipline-specific convention. Understanding and observing the disciplinary rhetorical choices and communication conventions will allow scientists to align the abstracts of their studies with the expectations of the targeted audience.